2017
DOI: 10.1007/s11695-017-2633-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Bariatric Patients Follow Dietary and Lifestyle Recommendations during the First Postoperative Year?

Abstract: Bariatric patients have medium to high adherence to the major lifestyle recommendations during the first year following LSG; however, adherence to those recommendations was not related to better weight loss at short-term follow-up. Adherence to recommended supplementation was associated with better micronutrient status 1 year postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 57 publications
2
25
0
1
Order By: Relevance
“…In a previous study, we observed associations between some bacterial changes and improvements in corpulence, metabolic or inflammatory markers, yet half of these associations are strongly dependent on food intake 49 . Dietary patterns also differ from one individual to another post-BS 25,26,46 and dietary recommendations between clinical centers may differ as well 51 . It is thus necessary to better examine the link between post-BS dietary intake and lifestyle changes (such as physical activity) and gut microbiota modulation to explain the reported variability in GM composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we observed associations between some bacterial changes and improvements in corpulence, metabolic or inflammatory markers, yet half of these associations are strongly dependent on food intake 49 . Dietary patterns also differ from one individual to another post-BS 25,26,46 and dietary recommendations between clinical centers may differ as well 51 . It is thus necessary to better examine the link between post-BS dietary intake and lifestyle changes (such as physical activity) and gut microbiota modulation to explain the reported variability in GM composition.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacterial genus changes such as Eubacterium spp, Ruminococcaceae spp and Faecalibaceterium spp, are associated with the amelioration of metabolic factors, including HbA1c. Moreover, the healthy diet recommended post-BS 24,46 might also play a role in increasing MGR, as proposed by Griffin et al, 16 .…”
Section: Bariatric Surgery and Gut Microbiota Modulation Microbial Rimentioning
confidence: 97%
“…Therefore, bariatric patients are advised to engage in regular physical activity [8][9][10][11]. Previous studies indicate that low physical activity after bariatric surgery is related to less weight loss and more weight regain [12][13][14], though more recent studies question whether weight loss is positively influenced by adherence to a healthy lifestyle with regular physical activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, psychosocial variables were not associated with the rate of weight loss in that study and other studies of one-year post-bariatric surgery patients (Fox et al, 2015). Adherence to dietary recommendations was not associated with weight loss during a short-term assessment of successful post-bariatric surgeries (Sherf-Dagan et al, 2017). There is thus a need to investigate the medium-term success of weight loss post-bariatric surgery, with special emphasis on dietary adherence and psychosocial variables.…”
Section: Introductionmentioning
confidence: 58%